The Effectiveness of Online Learning for Junior High School Students during the COVID-19 Pandemic on Student Learning Outcomes - Viriana Viriana (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2023)
This study investigated the effectiveness of online learning on the academic performance of junior high school students at SMP Negeri 48 Surabaya amidst the Covid-19 pandemic. As the primary instructional method, online learning utilized internet-based tools. The research design employed a pre-experimental approach with a single experimental group consisting of 42 students who were purposefully selected. The implementation of online learning followed the school’s guidelines. The results revealed a significant impact of online learning on student academic achievement, with a Sig. value of 0.004, supporting the alternative hypothesis (Ha). These findings underscore the importance of online learning as an alternative approach during challenging circumstances such as the pandemic. Educators, administrators, and policymakers can leverage these insights to enhance student learning outcomes. Further research is warranted to optimize the implementation of online learning for junior high school students in similar contexts. The study highlights the potential of online learning to address educational disruptions caused by unforeseen events like the Covid-19 pandemic. By integrating internet-based tools into the learning process, educators can provide continued access to education and support student achievement. These findings contribute to the growing body of knowledge on effective pedagogical approaches in times of crisis. Continued exploration and refinement of online learning strategies are necessary to ensure their effectiveness and relevance for junior high school students in similar circumstances.